2009
DOI: 10.2353/ajpath.2009.080599
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Fragmentation Promotes Oxidative Stress and Elevates Matrix Metalloproteinase-1 in Fibroblasts in Aged Human Skin

Abstract: Aged human skin is fragile because of fragmentation and loss of type I collagen fibrils, which confer strength and resiliency. We report here that dermal fibroblasts express increased levels of collagen-degrading matrix metalloproteinases-1 (MMP-1) in aged (>80 years old) compared with young (21 to 30 years old) human skin in vivo. Transcription factor AP-1 and ␣2␤1 integrin, which are key regulators of MMP-1 expression, are also elevated in fibroblasts in aged human skin in vivo. MMP-1 treatment of young skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
429
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 386 publications
(455 citation statements)
references
References 89 publications
16
429
1
9
Order By: Relevance
“…These enlarged fibroblasts produce increased levels of collagen and CTGF/CCN2. Interestingly, we recently reported that reduced fibroblast size/mechanical force also up‐regulates matrix metalloproteinase‐1 expression and thus causes collagen fibril fragmentation (Qin et al ., 2014), as observed in aged human skin in vivo (Fisher et al ., 2008, 2009). These data combined with our current findings provide a foundation for our understanding the cellular and molecular basis of age‐related loss of collagen production and increased collagen fragmentation in aged human skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These enlarged fibroblasts produce increased levels of collagen and CTGF/CCN2. Interestingly, we recently reported that reduced fibroblast size/mechanical force also up‐regulates matrix metalloproteinase‐1 expression and thus causes collagen fibril fragmentation (Qin et al ., 2014), as observed in aged human skin in vivo (Fisher et al ., 2008, 2009). These data combined with our current findings provide a foundation for our understanding the cellular and molecular basis of age‐related loss of collagen production and increased collagen fragmentation in aged human skin.…”
Section: Discussionmentioning
confidence: 99%
“…Cells between passage 3 and 10 were used for all experiments. 3D collagen lattices were prepared based on previous publication with minor modification (Fisher et al ., 2009). Briefly, neutralized rat tail type I collagen (2 mg mL −1 , BD, Biosciences) was suspended in medium cocktail [DMEM, NaHCO 3 (44 m m ), L‐glutamine (4 m m ), Folic Acid (9 m m ), and neutralized with 1N NaOH to pH 7.2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In pigs fed a high-cholesterol diet [31] the supplementation of vitamins C and E markedly prevents lipid peroxidation, increases neointimal collagen content, and reduces hypercholesterolaemiainduced changes in vascular MMP-1. The fibroblasts of aged human skin cultured in fragments, manifest raised intracellular oxidant levels; conversely, treatment with antioxidant MitoQ (10) significantly reduces MMP-1 expression [32]. The underlying mechanisms that have been discussed include: upregulation of the expression of genes involved in cell proliferation, regulation of transcription, as well as downregulation of genes involved in lipid metabolism, cell adhesion, and differentiation.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…In photoShuko Terazawa and Hiroaki Nakajima have contributed equally to this work. aged skin, there is a marked deficiency of HA (Margelin et al 1996;Takahashi et al 1995Takahashi et al , 1996 in addition to the fragmentation and loss of type I collagen fibrils due to the up-regulated activity of matrix-metalloproteinase (MMP)-1 (Fisher et al 2008(Fisher et al , 2009). Available evidence indicates that naturally aged, sun-protected skin and photoaged skin share important molecular features, including connective tissue damage, elevated matrix metalloproteinase levels and reduced collagen production (Varani et al 2001(Varani et al , 2002.…”
Section: Introductionmentioning
confidence: 99%